Risk Assessment of the Primary Reformer in the Ammonia Unit at Fertilizer Industry Using the HAZOP Method - Parapat, Riny Yolandha; Kylla Almira Rahma Fadillah; Risma Suci Novianti (Integrative Perspectives of Social and Science Journal, 2025)
One of the most critical units in the ammonia production process is the primary reformer. The primary reformer unit plays a crucial role in the production of ammonia through the steam methane reforming (SMR) process. Due to its high operating temperature and pressure, this unit poses significant safety risks, such as overpressure, catalyst damage, flame instability, and tube rupture. This study applies the Hazard and Operability Study (HAZOP) method to evaluate occupational health and safety risks within the primary reformer system. The HAZOP analysis was conducted by identifying critical nodes in the process and evaluating deviations based on key parameters such as pressure, temperature, flow rate, and composition. Using guide words like "No", "More", "Less", and "Reverse", various process deviations were assessed in terms of causes, consequences, safeguards, and recommended actions. The findings indicate that most risks arise from equipment malfunction, control system failure, or operator error. To mitigate these risks, several recommendations were proposed, including the addition of interlocks, redundant instrumentation, and regular calibration. The study concludes that the HAZOP method is effective in identifying hidden hazards and can significantly support improvements in occupational health and safety management in high-risk chemical process environments.